2006
DOI: 10.1016/j.mad.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of cristae in cardiac mitochondria of aged rat

Abstract: Interfibrillar mitochondria (IFM) of the heart in aged Fischer 344 rats show a biochemical defect which might be reflected in their morphology. We examined by high resolution scanning electron microscopy over 5,500 mitochondria to determine if a concomitant structural alteration existed. This methodology provides a means of examining mitochondrial cristae in three dimensions. Cristae of in situ subsarcolemmal mitochondria (SSM) and of IFM in both 6 and 24 month old Fischer rats are predominantly lamelliform. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 15 publications
3
33
0
2
Order By: Relevance
“…These findings complement those of Judge et al (56) who observed increased oxidative stress and antioxidant enzyme activities in the IFM of the aged rat heart. In addition, aging has been associated with a decrease in ETC complex III activity in the IFM of aged rat heart, which has been linked in part to a defect in the cytochrome c binding site of complex III (72), without effect on the IMM lipid environment or cristae morphology (53,68,87,107). Electron leakage at complex III, leading to increased superoxide production (86) and reduction in cytochrome oxidase subunit VIIa, was detected only in the IFM of aged rat hearts (35).…”
Section: Pathological Influencementioning
confidence: 99%
“…These findings complement those of Judge et al (56) who observed increased oxidative stress and antioxidant enzyme activities in the IFM of the aged rat heart. In addition, aging has been associated with a decrease in ETC complex III activity in the IFM of aged rat heart, which has been linked in part to a defect in the cytochrome c binding site of complex III (72), without effect on the IMM lipid environment or cristae morphology (53,68,87,107). Electron leakage at complex III, leading to increased superoxide production (86) and reduction in cytochrome oxidase subunit VIIa, was detected only in the IFM of aged rat hearts (35).…”
Section: Pathological Influencementioning
confidence: 99%
“…Por ende, la pérdida de la función mitocondrial, así como, de cardiomiocitos genera una reducción en la producción de la energía necesaria para el funcionamiento del corazón [30]. El Observatorio Nacional de Salud Colombiano [34] ha determinado que las enfermedades cardiovasculares fueron una de las principales causantes de muerte en Colombia en el periodo entre 1998 y 2011.…”
unclassified
“…Como ya se ha mencionado, el envejecimiento causa pérdida de la función mitocondrial, lo que conlleva a un aumento en la muerte de los cardiomiocitos a través de la liberación de factores apoptogénicos; proceso mediado por dichas mitocondrias disfuncionales. En el envejecimiento se presentan alteraciones bioquímicas en IFM; caracterizadas por una disminución en el rendimiento proteico, así como, en la velocidad de fosforilación oxidativa, mientras que las SSM, no presentan dichas alteraciones [30]. Sin embargo, en el estudio realizado por Hofer et al [40] en mitocondrias SSM e IFM aisladas de corazón de rata, determinaron que con la edad no hubo aumento en la generación de H 2 O 2 , ni disminución en la velocidad de consumo de oxígeno en IFM y SSM.…”
unclassified
“…Bloom and Fawcett, 1994), that mitochondria of such type of cells have tubular and vesicular cristae. Recently, (Riva et al, 2005;Riva et al, 2006) we have successfully applied our technique to investigate structural differences in two biochemically defined populations of isolated rat cardiac mitochondria, and to study the structure of cristae in relation to aging.As can be seen from Figure 8 we have been able to remove all cytoplasmic organelles of serous cells of salivary glands in order to expose the cytoplasmic side of the intercellular canaliculi. In the same preparations we demonstrated regular clusters of particles that we related to cellular junctions .…”
mentioning
confidence: 99%
“…Bloom and Fawcett, 1994), that mitochondria of such type of cells have tubular and vesicular cristae. Recently, (Riva et al, 2005;Riva et al, 2006) we have successfully applied our technique to investigate structural differences in two biochemically defined populations of isolated rat cardiac mitochondria, and to study the structure of cristae in relation to aging.…”
mentioning
confidence: 99%